2021
DOI: 10.1002/ptr.7036
|View full text |Cite
|
Sign up to set email alerts
|

Complementary effects of pine bark extract supplementation on inattention, impulsivity, and antioxidative status in children with attention‐deficit hyperactivity disorder: A double‐blinded randomized placebo‐controlled cross‐over study

Abstract: The purpose of this study was to investigate the complementary effects of polyphenolic compounds from pine bark extract (PE) as a strong antioxidative substrate on the symptoms of inattention and impulsivity in children with attention-deficit hyperactivity disorder (ADHD). This was a randomized, double-blind, crossover, placebo-controlled study that included two experimental units (4 weeks with PE supplementation and 4 weeks with placebo supplementation) separated by a 2-week washout period. ADHD participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The results of the risk of bias assessment are presented in Fig 3 . Among the 48 included studies, 29 studies provided specific methods for random allocation [ 31 34 , 36 39 , 41 , 45 63 , 78 ], and were therefore rated as having a low risk of bias in random allocation. Most of these studies employed computer random sequence allocation.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the risk of bias assessment are presented in Fig 3 . Among the 48 included studies, 29 studies provided specific methods for random allocation [ 31 34 , 36 39 , 41 , 45 63 , 78 ], and were therefore rated as having a low risk of bias in random allocation. Most of these studies employed computer random sequence allocation.…”
Section: Resultsmentioning
confidence: 99%
“…A significant reduction was also observed in the hyperactivity-impulsivity parameter after PBE supplementation compared to the baseline (p = 0.029) and compared to the placebo (p = 0.024). Moreover, the evaluation of inattention and impulsivity through the Conners Continuous Performance Test 3rd edition (CPT-III) revealed that the T-score of commissions was significantly reduced compared to the baseline after 4 weeks of PBE supplementation (p = 0.048) [25].…”
Section: Efficacy On Adhd Symptoms: Polyphenols Vs Traditional Drugs ...mentioning
confidence: 99%
“…The only opposite finding was detected by Tenenbaum and colleagues, who noticed no significant effects in the PBE group compared to the placebo. Finally, concerning the use of resveratrol as an add-on to methylphenidate, Rafeiy-Torghabeh et al showed significant results by revealing a decrease in the total scores and the inattention and hyperactivity subscores [24][25][26][27][28]; Table 2. ↓ after 8 weeks (17.60 to 4) Time-treatment interaction p = 0.036 Note: ↓ indicates a reduction; ↑ indicates an increase.…”
Section: Efficacy On Adhd Symptoms: Polyphenols Vs Traditional Drugs ...mentioning
confidence: 99%
“…17,[21][22][23][24][25] Compounds derived from natural sources have shown potential in ameliorating central nervous system disorders, including ADHD. 26,27 Theobromine (TB), a primary methylxanthine found in cacao beans and prevalent in cacao products like cocoa and dark chocolate, is one such compound. 28 Our previous research indicated that long-term TB supplementation enhances motor learning and working memory by increasing BDNF levels in the PFC of rodents 29,30 Additionally, chronic consumption of dark chocolate, rich in TB, has been reported to improve frontal lobe function in healthy adoles-cents.…”
Section: Introductionmentioning
confidence: 99%